Difusión de las memorias de sostenibilidad en Latinoamérica: análisis territorial y sectorial (2015)
This article has three objectives. First, to identify the geographical and sectorial distribution of sustainability reporting in Latin America using the Global Reporting Initiative. Second, to compare this diffusion pattern with the pattern of global outreach in order to identify similarities and differences. Finally, a forecast of future dissemination in the region. Regressions of the data from the Global Reporting Initiative available in Latin American countries were performed using the logistic curve as pattern. Further indicators of concentration and instability of the time series are used. It is concluded that the Global Reporting Initiative standard has been moderately adopted by companies in Latin America. Moreover, significant differences are observed in the development of the social responsibility of organizations across countries.